THU0069 Increased rate of diastolic heart failure in rheumatoid arthritis correlates with systemic inflammation and persistent disease activity, independent from treatment strategy. (23rd January 2014) - Gottwald, M.; Schau, T.; Neuss, M.; Ridjab, D.; Fischer, I.; Butter, C.; Zaenker, M.
Abstract : Background: Increased prevalence of chronic heart failure is observed in patients with rheumatoid arthritis (RA) and heart failure with normal ejection fraction (HFNEF) is the predominant type. Although traditional cardiovascular risk factors are overrepresented in RA patients, they alone do not sufficiently explain higher morbidity. Chronic inflammation is a suspected contributor to myocardial dysfunction. Further data is necessary to elucidate the influence of persistent RA disease activity and RA treatment on HFNEF. Objectives: To correlate clinical signs, laboratory findings and echocardiographic markers of heart failure in a well-characterized cohort of RA-patients with cardiovascular risk factors and comorbidity Methods: Prospective cross-sectional study including all RA-patients consecutively treated in our community based outpatient-clinic in a 3 months period. Inclusion criteria were written consent and diagnosis of RA, fulfilling ACR/EULAR-criteria. All patients were interviewed using a standardized questionnaire. Clinical signs were evaluated based upon Framingham criteria. Laboratory tests included NT-proBNP. Echocardiography contained tissue doppler and global longitudinal strain (GLS) imaging. Results: 162 patients with RA, n=110 (68%) female, mean (SD) age 61.3 (±13.1) years, mean disease duration 12.5 (±11.4) years, mean DAS28 2.8 (±1.0), mean FFbH 68 (±27)%, mean HAQ 1.3 (±0.9) were included. Rate of remission or low-disease-activity (DAS28 and lower remission rates in the biologic groups according to more severe disease state and longer disease duration. However, no significantly differences were found for HFNEF rates and cardiovascular comorbidity. Conclusions: Traditional risk factors as well as RA-related factors are responsible for HFNEF in RA. RA-duration, persistent disease activity with DAS28 >2.6, increased ESR as markers of chronic inflammation were shown to be significant and independent contributors. The reduced GLS in HFNEF patients supports a putative role of endomyocardial fibrosis as a link between inflammation and impaired myocardial function. Disclosure of Interest: None Declared